The Research of Customer Switching Behavior at Some Leasing Companies - Arafah, Willy; Mutis, Thoby (International Review of Management and Marketing, 2018)
The goals of this research was to examine and analyze the impact of price, service quality, effective advertising competition, involuntary factors, distance to customer switching behavior. This research was expected to benefit the some leasing companies in Indonesia (PT. FIF, PT. ADMF, Tbk, PT. SOF, PT. WOM, PT. BAF). The design of this research apply hypothesis testing using a quantitative methods, hypothesis testing, which generally describes the characteristics of certain relationships or differences between groups or interdependence of the two factors or more data analysis applied measuring method structural equation modeling (SEM). The questionnaire given to the sample directly as much as 300 customers of leasing companies will be used in this research. Survey method by intercepting customers who leave the leasing company because it provides the advantage of taking data directly. The results of research indicate that the factors influence price, service quality, effective advertising competition, Involuntary factors, distance is very influential on the displacement behavior some leasing companies in Indonesia. Keywords: Effective advertising competition, switching involuntary, distance, service quality, price. JEL Classification: M3